On Nonlinear Vekua Type Equations - Rogosin, S. V. (Nonlinear Analysis: Modelling and Control, 2006)
Nonlinear Vekua-Bers type differential equations are studied on the base of certain methods of nonlinear analysis. A survey of recent results in the area is presented.